Liderazgo educativo docente y su influencia en la participación activa de los estudiantes del primer año de Bachillerato, del Colegio de Bachillerato Beatriz Cueva de Ayora. Periodo 2023-2024 - Gálvez Cordero, Karen Stefanny (2024)
The aim of this research is to analyze the impact of educational leadership among teachers and its influence on students' active participation during the classroom learning process. It is constructed using a mixed-method approach, which relies on descriptive statistics for result analysis. Data collection involved administering a survey to teachers to understand their perspective on educational leadership, and likewise, a Likert-scale survey was administered to students to comprehend their perspective on teachers' educational leadership and its influence on the learning process. Twelve teachers who are involved in the teaching process of the "F" grade level of high school, as well as 27 students from the same class, who evaluated the teaching role as leadership in the classroom, participated in the research process. The results indicate that at the Beatriz Cueva de Ayora High School, teachers were described through their students' perceptions, which indicate that they possess traits of transformational, emotional, shared, and participative leadership. Additionally, it is highlighted that the crucial role of teachers is to serve as role models influencing students' engagement and motivation in the classroom.